Developing an alternative crossbar material from jute/E-glass fiber hybrid reinforced polymer matrix composite - Gadisa, Dejene Girma; Tesfay, Abrha Gebregergs (International journal for simulation and multidisciplinary design optimization, 2024)
Over the last three decades, the use of hybrid reinforced fiber composite materials for structural applications has increased. Minimizing the weight of vehicle components has been considered an important solution for improving fuel economy, increasing technical benefits, and reducing harmful emissions. This study used jute and E-glass fiber with a polyester matrix to develop the hybrid composite. Hand layups were employed for sample preparation of 40% fiber and 60% of the polyester matrix with four different stacking sequences. The mechanical property and water absorption test were influenced by fiber stacking sequences and jute fiber treatment. In this investigation, the result shows that the hybrid G-J-J-G hybrid of NaOH-treated jute fiber exhibited higher strength than a hybrid containing jute fiber at their outer layer and a hybrid of the same stacking sequence with untreated jute fibers. A hybrid with a G-J-J-G arrangement was used to develop alternative crossbar members by size optimization with a genetic algorithm. The sizing optimization of crossbar member results shows that the weight of the hybrid composite crossbar can be reduced by 46.47%, from 9.765 kg to 5.227 kg per single component of crossbar member, and comparatively, an average of 0.00544 L per 100 km of fuel was enabled to be saved. Thus, jute/E-glass hybrid reinforced polyester composite can effectively be an alternative to the current steel structure without compromising their application.